Faktor-Faktor Penentu Niat Kewirausahaan: Peran Mediasi Efikasi Diri Teknopreneurial di Kalangan Mahasiswa Pendidikan Ilmu Sosial - Zalma Niendya Pangestika; Rusdarti (Universitas Negeri Semarang, 2026)
Entrepreneurial intention is the strongest predictor of actual entrepreneurial behavior, preceded by planned and conscious intention. According to survey data on the number of students involved in entrepreneurship in the field of social science education, Faculty of Teacher Training and Education, University of Lampung, student awareness of entrepreneurship is still low. Therefore, it is necessary to increase students' entrepreneurial intention. This study aims to examine the effect of entrepreneurial knowledge, digital literacy, and entrepreneurial motivation on entrepreneurial intention through technopreneurial self-efficacy. The population in this study consisted of 428 students from the Department of Social Science Education, Faculty of Teacher Training and Education, class of 2022, University of Lampung. The sample size was determined using the Slovin formula, resulting in 207 respondents. The sampling technique used was proportional random sampling. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data analysis techniques used included descriptive analysis, path analysis, and the Sobel test. The results of the study showed that (1) entrepreneurial knowledge, digital literacy, and entrepreneurial motivation influence technopreneurial self-efficacy; (2) entrepreneurial knowledge, digital literacy, and entrepreneurial motivation influence entrepreneurial intentions through technopreneurial self-efficacy; (3) technopreneurial self-efficacy influences entrepreneurial intentions. This research is expected to contribute to the development of scientific knowledge and test the theory of planned behavior related to entrepreneurial intentions